46.3: Development of Source/Drain Electrodes for Amorphous Indium Gallium Zinc Oxide Thin Film Transistors. Issue 1 (1st July 2013) - Chen, Yuting; Wu, Jie; Dong, Chengyuan; Shi, Junfei; Zhan, Runze; Chiang, Cheng‐Lung; Chen, Po‐Lin; Lai, Tzu‐Chieh
Abstract Tantalum etched by H2O2 solution shows best performance to be the source/drain electrodes of inverted staggered amorphous Indium Gallium Zinc Oxide thin film transistors among the investigated five metal materials. In addition, the etching property is improved significantly by adding aqueous ammonia properly.